A comparison of Mini-FLOTAC and McMaster techniques in detecting gastrointestinal parasites in West Africa Dwarf sheep and goats and crossbreed rabbits. Issue 1 (1st January 2021) - Alowanou, Géorcelin G.; Adenilé, Adam D.; Akouèdegni, Guénolé C.; Bossou, Arsène C.; Zinsou, Fréjus T.; Akakpo, Gilles-Christ A.; Kifouly, Habirou A.; Rinaldi, Laura; von Samson-Himmelstjerma, Georg; Cringoli, Giuseppe; Hounzangbé-Adoté, Sylvie
ABSTRACT: McMaster (McM) method is one of the most widely used techniques for the assessment of faecal parasites shedding in veterinary practices because of its simplicity. However, due to its light sensitivity, recently, the Mini-FLOTAC (MF) has been introduced as a possible alternative for faecal worm egg counts. This study aims to compare the diagnosis performance of MF to McM technique. Faecal samples from 40 animals randomly selected in sheep, goats and rabbits' farms were collected and examined individually using MF and McM techniques. A statistical difference ( p < 0.001) in strongylida egg counts in small ruminants and oocyst of Eimeria spp counts in rabbits using both techniques was observed. However, strongylida eggs per gram of feces in sheep (MF: 202.01 vs McM: 174.75) goat (MF: 147.36 vs McM: 143.75) and oocysts of Eimeria spp per gram of feces in rabbits (MF: 130.75 vs McM: 130.5) revealed no significant difference ( p > 0.05). MF showed better diagnostic performance in term of the prevalence (MF: 32.5–100% vs McM: 7.5–70%) and the precision values (MF: 85.52–90.44% vs McM: 49.52–63.07%). This study demonstrated that MF appears to be the more reliable alternative technique for veterinary practices.